Eficacia del Bórax como inhibidor de Cándida albicans in vitro, UAN sede Ibagué 2022 (2022)
Background. There are different factors that develop subprosthetic stomatitis, in studies carried out on prostheses, the growth and development of Candida albicans, known as a yeast fungus, was found in the geriatric population. Goal. This study is to describe the efficacy of Boráx as an inhibitor of Candida albicans in vitro. Method. The research consisted of a quantitative and qualitative experimental study on the antifungal activity of Boráx, samples of Candida albicans were previously obtained in prosthetics from patients with grade I and grade III denture stomatitis. In the development of this study, resolution 8430 of 1993 Ministry of Health will be taken into account, which establishes the scientific, technical and administrative standards for research in the health area. Results. A significant discrepancy was obtained between the different percentages of Boráx and days in which the culture media were studied, thus giving a response from the three concentrations where it was observed that after 8, 15, and 20 days of testing with the Boráx yielded as a result a greater inhibitory efficacy in a percentage of 15%. Conclusions. The inhibitory action of Boráx at different concentrations was demonstrated, being 15% the most effective in the antifungal action against Candida albicans